Effect of Trikafta on bone density, body composition and exercise capacity in CF: A pilot study. Issue 2 (22nd November 2022) - Gur, Michal; Bar–Yoseph, Ronen; Hanna, Moneera; Abboud, Dana; Keidar, Zohar; Palchan, Tala; Toukan, Yazeed; Masarweh, Kamal; Alisha, Irit; Zuckerman‐Levin, Nehama; Bentur, Lea
Abstract: Background: While the positive effect of Trikafta on cystic fibrosis (CF) pulmonary disease is well established, there is limited data about its effect on bone mineral density (BMD), body composition and exercise capacity. Methods: A pilot single center study. BMD and body composition were measured three months after the initiation of Trikafta (study group) and compared to values obtained 2 years earlier. CF patients not treated with Trikafta, for whom BMD was measured 2 years apart, served as controls. Spirometry, lung clearance index (LCI), sweat test, six‐min walk test (6MWT) and cardio‐pulmonary exercise test (CPET) were performed before and three months after the initiation of Trikafta. Results: Nine study patients, aged 18.6 ± 4.7 years, and nine controls. For the study group, BMI and hip and spine BMD increased significantly (19.4 ± 2.6 to 20.3 ± 2.19 BMI, p = 0.05; 0.73 ± 0.098 to 0.81 ± 0.12 gr/cm 2 hip, p = 0.017; 0.76 ± 0.14 to 0.82 ± 0.14 gr/cm 2 spine, p = 0.025). For the control group, there was no difference in hip or spine BMD. Lean body mass, %fat z‐score and fat mass/height 2 z‐score increased significantly (34770.23 ± 10521.21 to 37430.16 ± 10330.09gr, p = 0.017; –0.8 ± 0.75 to 0.46 ± 0.58, p = 0.012; and −0.98 ± 0.66 to −0.04 ± 0.51, p = 0.025, respectively). 6MWT improved from 541.1 ± 48.9 to 592.9 ± 54.5 m ( p = 0.046). As expected, FEV1%pred increased ( p = 0.008) and sweat chloride decreased significantly ( p = 0.017). In CPET, VE/VCO2 improved, indicating better ventilatory efficiency. Conclusions: To the best of our knowledge, this is the first study evaluating the metabolic effects of Trikafta. The results are encouraging and offer hope beyond the well‐established effect on pulmonary disease. Larger long‐term studies are warranted to unpin the underlying physiological mechanisms.